**1. Find the zeroes of the following quadratic polynomials and verify the relationship between the zeroes and the coefficients.**

(iii) 6x² – 3 – 7x

(iii) 6x² – 3 – 7x

Factorize the equation

6x² – 7x – 3

Compare the equation with ax² + bx + c = 0

We get

a = 6 ,b=-7 c= -3

To factorize the value we have to find two value which

sum is equal to b =-7

product is a x c = 6 x -3 = -18

2 and -9 are such number which

sum is 2 – 9 = - 7

product is 2 x - 9 = - 18

So we can write middle term -7x = 2x – 9x

We get

6x² + 2x - 9x - 3 = 0

2x(3x + 1) -3(3x + 1) = 0

(3x + 1) (2x - 3) = 0

3x + 1 = 0 , 2x - 3 = 0

Solve for first zero

3x = - 1

x = -1/3

Solve for second zero

2x-3 = 0

2x = 3

X = 3/2

Plug the values of a , b and c we get

Sum of zeros -b/a = -(-7/6) = 7/6

Product of zero c/a = -3/6 = -1/2